'Snitches get stitches': School-specific barriers to victim disclosure and peer reporting of sexual harm committed by young people in school contexts. (March 2019) - Allnock, Debra; Atkinson, Ruth
Abstract: Background: School based, peer-to-peer sexual harm is under-researched despite its prevalence and adverse effects on young people across the globe. Understanding barriers to victim disclosure and peer reporting might help towards the prevention and protection of young people. Objective: This study explores dual perspectives of young people and educational staff about school-specific environmental barriers to 1) young people's disclosure of sexual harm experienced, and 2) young people's reporting of sexual harm on behalf of others. Participants and setting: Participants include 59 young people aged 13–21 and 58 educational staff, drawn from seven schools across four local authorities in England whom formed part of a wider study on harmful sexual behavior and safety in schools. Methods: Focus groups were carried out with young people and education staff. The sessions were thematically analysed and focused on barriers to disclosure within the school context. Results: Peer groups set powerful 'rules' that influence the ability and willingness of young people to report sexual harm. Some school responses for addressing sexual harm are sub-optimal and sexual harm is not adequately prioritised. Some schools appear to struggle to manage more subtle forms of sexual harm compared with more recognized forms of violence and abuse. A significant proportion of sexual harm is so prevalent that it is 'normalised', and therefore under-reported. This resigned acceptance to sexual harm consequently shapes young people's disclosures. Conclusions: School systems of responding to sexual harm require strengthening to increase feelings of safety and empowerment of young people.